PERAN PERGURAN TINGGI : MENINGKATKAN KOMPETENSI PENGELOLA KOPERASI MELALUI COMPETENCY BASED TRAINING - R. Rosiyana Dewi; Hexana Sri Lastanti; Sofie Sofie; Murtanto Murtanto (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2019)
Cooperatives is a business activity has many benefits for the welfare of the community, especially its members, and can indirectly improve the nation's economy. Accounting records and tax calculations are required so that the financial information they convey can be used in decision making. Community Service (Pengabdian Kepada Masyarakat) conducted by Trisakti University's Faculty of Economics and Business in collaboration with the PusKop KWU Army (AD) which was held for 4 days at the Campus F FEB of Trisakti University, on 27-30 August 2018, with 46 participants. Activities in the form of competency-based training include 7 units material of junior accounting technician competencies, namely professional practice in work, occupational health and safety, journal entry processing, general ledger processing, financial reporting, and computerized accounting. It also provided material on taxation. The results of this activity are very helpful for management and employees of cooperatives in presenting quality cooperative financial reports as a form of accountability of cooperative managers to their members. The results of this competency-based training received very good ratings from participants of this competency-based training.